Revitalisasi Tempat Pembuangan Sampah Sementara Di Perumahan Buana Gardenia Untuk Peningkatan Kesehatan Lingkungan - Dyah Pratiwi Kusumastuti; Indah Handayasari; Irma Sepriyanna; Hastanto Sm (Sekolah Tinggi Teknik - PLN, 2020)
A comfortable and healthy residential area must be supported by the availability of adequate facilities and infrastructure such as the availability of clean water networks, road networks, drainage systems, worship facilities, green open spaces and temporary garbage storage facilities. The available temporary garbage collection sites must be able to accommodate the volume of waste up to the relevant transportation service schedule. However, sometimes transportation delays can occur, so that it can cause problems in residential areas, especially in Buana Gardenia housing such as unpleasant odors and the flow of water that is blocked due to rubbish that falls into the waterways. Waste that falls into the water channel over time can clog the flow of water in it, other than that due to organic rotting in the water channel can cause sedimentation in the bottom of the channel so that the channel becomes shallow. To anticipate the fall of rubbish into the waterways due to the full volume of waste and delays in transportation from related agencies. In the community service activities at the Buana Gardenia housing complex, a temporary garbage shelter will be revitalized. The revitalization results can reduce the waste that falls into the water channel so that the flow of water in the channel flows smoothly, reducing the number of mosquito larvae and puddle when it rains.